Empire's workshop Latin America, the United States, and the rise of the new imperialism [with a new afterword on the Obama doctrine] - Grandin, Greg, 1962- (New York Metropolitan Books/Henry Holt and Company, 2010)
The camel not in the Koran -- How Latin America saved the United States from itself -- The most important place in the world: toward a new imperialism -- Going primitive: the violence of the new imperialism -- Bringing it all back home: the politics of the new imperialism -- The third conquest of Latin America: the economics of the new imperialism -- Globalization's showpiece: The failure of the new imperialism -- Iraq is not Arabic for Latin America
A Holt paperback.
Includes bibliographical references [253]-284) and index
Donated by Prof. M. Riley 1.19.16
Keywords: Americans -- Latin America -- History; Imperialism; Latin America -- Relations -- United States; United States -- Relations -- Latin America; United States -- Foreign relations -- 2001-2009 -- Philosophy